Biblical archetextuality in F. Hölderlin’s poetry - Sinilo, Galina V. (Journal of the Belarusian State University. Philology, 2020)
This paper examines the problem of biblical archetextuality in the poetry of the great German poet and innovator Friedrich Hölderlin (1770–1843), whose work is the result of a fruitful synthesis of antique (primarily Hellenic), biblical, and also German tradition proper. We show that at the mature stage of creativity, Hellenic «statics of form» is relevant for Hölderlin, then at the later – biblical «dynamics of power» (S. S. Averintsev). We affirm that, especially at the late stage of the German poet’s creative career, The Bible plays the role of an «axial» archetext – a meaningful and text-generating text. Moreover, prophetic and apocalyptic writings, Gospel texts are most significant for Hölderlin, and from the lyric books of The Bible – The Psalter. We show that for Hölderlin the mystical concept of total unity turns out to be extremely important, defining the main meanings and codes of his artistic world and related to Christian and Jewish mysticism. For Hölderlin, the concept of Love as a force connecting and transforming the world and man, and the concept of the poet as a relay of the Divine Word and a mediator between the earthly and heavenly worlds are also extremely significant. The poet’s mission is akin to the prophetic. He brings God’s Word, the God’s Law to people and, using a poetic gift, constitutes earthly being, transforming the transient into the abiding eternally. Biblical archetextuality is also reflected in poetic syntax (striving for brevity and amplification, rigid concatenation of words without pretexts, an abundance of genitive definitions, the preference for parataxis to hypotaxis) and, in general, in the language of Hölderlin’s later philosophical hymns, written in free rhythms.
Keywords: Friedrich Hölderlin; The Bible; «axial» archetextuality; concept of total unity; Christian and Jewish mysticism; philosophical hymn; amplification; parataxis; free rhythms; 18th century German poetry